The immunomorphological features of cervical intraepithelial neoplasia associated with HPV infection depending on the type of infertility - Е. О. Kindrativ (Patologìâ)
Aim. Objective was to establish the features of markers expression of receptivity, proliferation, apoptosis and angiogenesis of cervix with CIN associated with HPV infection in various forms of female infertility.